Effect of sintering temperature on microstructure, crystal structure and dielectric performance of Ba0.67Sr0.33TiO3 ceramics prepared by a novel direct coagulation casting via high valence counter ions (DCC-HVCI) method. Issue 3 (1st February 2021) - Lu, Lu; Chen, An-Nan; Chen, Ying; Cheng, Li-Jin; Wu, Jia-Min; Liu, Rong-Zhen; Shi, Yu-Sheng
Abstract: Perovskite Ba0.67 Sr0.33 TiO3 (BST) ceramics with improved dielectric performance were fabricated by a novel direct coagulation casting via high valence counter ions (DCC-HVCI) method using 0.5 mol% MgO as the coagulation agent. The influence of sintering temperature on micromorphology, crystal structure, and dielectric performance of BST ceramic components was systematically evaluated. The densification rate of BST samples could reach the maximum at a heating temperature around 1305 °C and end up approximately at 1380 °C. As increasing the sintering temperature from 1400 to 1550 °C, the relative density of BST ceramics decreases from 98.82 ± 0.16% to 96.72 ± 0.06%, and the mean grain size drops gradually from 9.96 to 4.68 μm. The increased sintering temperature promotes the lattice expansion due to Ti 4+ replacement at B site by Mg 2+, as well as the generation of oxygen vacancies. In addition, as increasing sintering temperature, the dielectric permittivity (εr ) of BST ceramic components decreases first and then slightly increases, while the dielectric loss (tanδ) of ceramics shows the opposite trend. The results indicate that the initial tanδ increase is mainly attributed to the lattice expansion of BST ceramics, and the subsequent loss reduction results from the easily localized conduction electrons on Mg 2+ sites reducing the carrier concentration. The samples sintered at 1550 °C show the lowest dielectric loss (tanδ≈0.013), which is significantly reduced by an order of magnitude compared with that of dry-pressed samples (tanδ≈0.262).